Parallel reorthogonalization of the qr decomposition after deleting columns - Clarke, Michael R B; Kontoghiorghes, Erricos John (My University, 1993)
In this note we propose a method based on compound disjoint Given's rotations, for reorthogonalizing the QR decomposition after deleting columns.
Keywords: Algorithms; Parallel algorithms; Columns